BIOM-08. DNA METHYLATION-BASED SUBGROUPING PREDICTS SURVIVAL BENEFIT FROM LOMUSTINE/TEMOZOLOMID COMBINATION THERAPY IN MGMT PROMOTOR-METHYLATED GLIOBLASTOMA. (12th November 2021) - Weller, Johannes; Waha, Andreas; Schneider, Matthias; Seidel, Clemens; Steinbach, Joachim; Hau, Peter; Schlegel, Uwe; Tonn, Jörg-Christian; Grauer, Oliver; Sabel, Michael; Krex, Dietmar; Schnell, Oliver; et al.
Abstract: BACKGROUND: The CeTeG/NOA-09 trial showed that lomustine/temozolomide chemotherapy prolongs survival for newly diagnosed MGMT-methylated glioblastoma patients. Previous reports on temozolomide monotherapy suggested, that the survival benefit of temozolomide in MGMT-methylated tumors may be restricted to the RTK II methylation subgroup and absent in RTK I and MES subgroups. To identify patients with a particularly strong benefit from CCNU/TMZ, we explored the association of methylation subgroups with outcome after lomustine/temozolomide therapy. METHODS: All patients from the CeTeG/NOA-09 trial with sufficiently available tumor tissue (n = 98) underwent 850K methylation array analysis of their tumor and methylation subgroup annotation (Heidelberg brain tumor methylation classifier v11b4; calibrated score > 0.5 required). Overall survival (OS) was compared between a pooled cohort of tumors of the RTK I/MES subgroups and RTK II tumors. RESULTS: In the CCNU/TMZ arm of CeTeG/NOA-09, OS was prolonged in RTK I/MES (n = 16; median not reached, 4-year OS 69%) as compared to RTK II patients (n = 14; median 20.6 months, 4-year OS 23%; p = 0.004 logrank test). In the standard temozolomide arm of CeTeG/NOA-09, OS tended to be shorter in RTK I/MES (n = 7; median 23.7 months, 4-year OS 17%) as compared to RTK II patients (n = 17; median 35.2 months; 4-year OS 38%, p = 0.15). CONCLUSION: The CCNU/TMZ-dependent survival prolongation in patients with RTK I/MES tumors as opposed to RTK II seen in CeTeG/NOA-09 suggests that methylation-based subgrouping could be predictive for CCNU/TMZ efficacy in newly diagnosed MGMT-methylated glioblastoma.